Prevalence of Antibody to Current Influenza Viruses and Effect of Vaccination on Antibody Response. Issue 5842 (23rd December 1972) - Pereira, Marguerite S.; Chakraverty, Pratima; Schild, G. C.; Coleman, Marion T.; Dowdle, W. R.
Abstract : The extent of antibody to the influenza virus A/Hong Kong/68 (H3N2) after four years of prevalence was investigated in Britain and in the U.S.A. The results indicated a high incidence in both populations. The prevalence of antibody to a variant A/England/42/72 (H3N2) which has been causing epidemics of influenza in the southern hemisphere during the middle months of 1972 was also investigated. The differences reflect the shift in antigenic content of this variant, and although the overall proportion of the sera with antibody at > 1/40 was 37%, some age groups had an incidence of only 20% or less with antibody at this level. A commercial inactivated A/Hong Kong/68 influenza vaccine was given to a group of volunteers in Britain to see how effective it might be in stimulating antibody to the variant A/England/42/72. The antibody responses were better than expected from earlier vaccine studies, and 63% of the vaccinees developed antibody to the A/England/42/72 to levels thought likely to be protective. This suggested that until a vaccine made with the variant A/England/42/72 becomes available the present A/Hong Kong/68 vaccine would be of use to protect those at special risk this winter.